Gene regulation of filaggrin and other skin barrier proteins via aryl hydrocarbon receptor. Issue 2 (November 2015) - Furue, Masutaka; Tsuji, Gaku; Mitoma, Chikage; Nakahara, Takeshi; Chiba, Takahito; Morino-Koga, Saori; Uchi, Hiroshi
Highlights: Aryl hydrocarbon receptor (AHR) is a sensor for low molecular weight chemicals. Ligand activation of AHR induces gene expression of filaggrin. Dioxins and antioxidant phytochemicals are AHR ligands. Both oxidative and antioxidant ligands induce gene expression of filaggrin. Abstract: Aryl hydrocarbon receptor (AHR) is a ligand-dependent transcription factor that binds to structurally diverse chemicals including dioxins, coal tar, flavonoids and tryptophan photoproducts. Upon ligation, cytoplasmic AHR translocates to the nucleus, heterodimerizes with aryl hydrocarbon receptor nuclear translocator and mediates numerous biological effects by inducing the transcription of various AHR-responsive genes such as epidermal barrier proteins. The activation of AHR usually generates oxidative stress. However, AHR also mediates antioxidant signaling by a plethora of ligands via nuclear factor-erythroid 2-related factor-2. Both oxidative and antioxidant ligands upregulate the expression of the filaggrin gene. We review the role of AHR signaling in the gene regulation of epidermal barrier proteins.